CORRELATIONS OF GEO-ELECTRICAL RESISTIVITY WITH GEOTECHNICAL SOIL PARAMETERS - JUSOH, MUHAMMAD NOOR HISYAM (2019)
Soil boring and sampling for site investigation is generally used for subsurface profiling and geotechnical calculations